(NwYSOKOTEMPERATURNAQ KRISTALLOHIMIQ (B:s (NtEORIQ(B, (NMETODY I REZULXTATY ISSLEDOWANIJ (B/s - (NfILATOW(B, (NsTANISLAW kONSTANTINOWI^s ((Nl(B. :s (NnEDRA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 270-280 (264 (NNAZW(B.)s
(NuKAZ(B. (NFORMUL(B. (NI MINERALOW(B: (NS(B. 281-285s
Keywords: (NkRISTALLOHIMIQs; (NmINERALY (B- (NkRISTALLI^ESKAQ STRUKTURAs